Recent New Zealand deep-water benthic foraminifera - Bruce William Hayward (PANGAEA, 2022)
A total of 563 species is listed from deep water (>50 m) from the New Zealand Exclusive Economic Zone (EEZ). The 347 most common or distinctive species are fully illustrated and their diagnostic features outlined. The dataset gives census counts of benthic foraminifera and sample locality and proxy data.